Towards a theory of ethnic separatism : a case study of Muslims in the Philippines - Ortiz, Alan Tormis (Michigan : UMI, 1986)
Thesis (Ph.D) -- University of Pennsylvania, 1986
Keywords: Muslims -- Philippines